MODEL DIRECT INSTRUCTION DENGAN TEKNIK PROBING PROMPTING : DAMPAK TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMA NEGERI 4 LUBUKLINGGAU TAHUN PELAJARAN 2018/2019 - Nina Trisna; Tri Ariani (LP4MK STKIP PGRI Lubuklinggau, 2019)
This study aims to determine the completeness of the learning outcomes of Class X students after applying the Direct Instruction model with Prompting Probing techniques in 4 Lubuklinggau Public High Schools in 2018/2019 Academic Year significantly. This type of research is quasi-experimental research carried out without a comparison class. The design used in this study was one group pre-test post-test. The population in the study was all class X students of SMA Negeri 4 Lubuklinggau, amounting to 143 students. Samples were taken randomly, obtained class X.MIA 2, which amounted to 36 students as samples. Data collection is done by test technique. The collected data was analyzed using the t-test at a significant level α = 0.05. Based on the results of data analysis, it can be concluded that the results of physics learning in class X of SMA Negeri 4 Lubuklinggau after the Probing Prompting technique were applied were significantly completed. The average score of students' final test is 75.11 and the percentage of students who complete is 80.5%.